2021
DOI: 10.1371/journal.pone.0255508
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of tourism development in China’s major cities under the constraint of PM2.5

Abstract: Climate / weather factors are important factors for tourists to choose tourist destinations. With the public’s attention to the influence of haze, air quality will have a profound impact on the development of tourism in tourist destinations. Based on the Epsilon-based Measure (EBM) super-efficiency model and Global Malmquist–Luenberger index analysis method, this paper aims to study the tourism development efficiency of 58 major cities in China from 2001 to 2016 and analyse the total factor productivity in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…These policies help Singapore better respond to risks and promote the supporting role of tourism development for other sectors. This conclusion is supported by Li, Duan et al [54], who confirmed that tourism development efficiency of 58 China's cities is increasing year by year.…”
Section: Plos Onementioning
confidence: 75%
“…These policies help Singapore better respond to risks and promote the supporting role of tourism development for other sectors. This conclusion is supported by Li, Duan et al [54], who confirmed that tourism development efficiency of 58 China's cities is increasing year by year.…”
Section: Plos Onementioning
confidence: 75%
“…The results related to air quality corroborate with Zhou et al [ 103 ] who also reported a negative impact of low air quality on tourism. Li et al [ 104 ] also found a considerable effect of PM2.5 on tourism in China. Moreover, Zhang et al [ 53 ] and Becken et al [ 54 ] also described the importance of air quality on tourism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on tourism suitability have involved the assessment and simulation of environmental factors, mainly from the aspects of climate comfort (Yang et al, 2018) and ecological environment level (Dhami et al, 2017; Ayhan et al, 2020). In addition, tourists are also very concerned about the environmental factors that affect health (Li et al, 2021). On the basis of previous studies, this study comprehensively evaluates the tourism environmental suitability of China from the three aspects of weather conditions, vegetation status, and health effects.…”
Section: Research Areas and Data Sourcesmentioning
confidence: 99%